2008
DOI: 10.1152/ajpregu.90327.2008
|View full text |Cite
|
Sign up to set email alerts
|

Salmon calcitonin reduces food intake through changes in meal sizes in male rhesus monkeys

Abstract: Bello NT, Kemm MH, Moran TH. Salmon calcitonin reduces food intake through changes in meal sizes in male rhesus monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
4
9
0
1
Order By: Relevance
“…However, sCT decreased both short-term and long-term (1-and 24-hour values) food intake in high alcohol-consuming rats, which was accompanied by a decrease in body weight. The shortterm effect of sCT on food intake in the low alcohol consumers is compatible with other food intake studies, where various doses of sCT suppress food intake in a dose-dependent manner, showing the most robust effect on the first meal size (Bello et al 2008). Moreover, the present results are in accordance with previous studies that have established an anorexigenic effect of the activation of amylin receptors (Reda et al 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, sCT decreased both short-term and long-term (1-and 24-hour values) food intake in high alcohol-consuming rats, which was accompanied by a decrease in body weight. The shortterm effect of sCT on food intake in the low alcohol consumers is compatible with other food intake studies, where various doses of sCT suppress food intake in a dose-dependent manner, showing the most robust effect on the first meal size (Bello et al 2008). Moreover, the present results are in accordance with previous studies that have established an anorexigenic effect of the activation of amylin receptors (Reda et al 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Our data revealed that a low dose of sCT (1 μg/kg) did not block but presented a dosedependent effect in regard to alcohol-induced locomotor stimulation. Experiments in rhesus monkeys have showed that administration of lower doses of sCT, in the range of 0.032 to 1 μg/kg, decreases food intake in a dose-response manner (Bello, Kemm, & Moran 2008), suggesting a potential enhanced effect of higher doses of the drug. However, the absence of significant sCT effect in our locomotor activity experiments could potentially be explained by the requirement of higher doses of sCT in order to exert its alcohol antagonizing effects.…”
Section: Discussionmentioning
confidence: 99%
“…VTA knockdown of CTR-A expression was confirmed via qPCR (e). with systemic amylin's satiating properties (Bello et al, 2008;Lutz, 2005;Lutz et al, 1995b). Along with the current findings indicating a role for NAcC DA signaling in VTA amylin-mediated control of feeding, these data suggest that VTA AmyR activation may engage common physiological (DA) and behavioral (meal size) mechanisms to produce the suppression of intake of both palatable and bland foods by VTA AmyR activation.…”
Section: Discussionsupporting
confidence: 76%
“…Systemic administration of amylin and amylin agonists such as salmon calcitonin (sCT) and pramlintide reduce food intake and body weight in humans and animal models (Bello et al, 2008;Chapman et al, 2005;Lutz et al, 1994Lutz et al, , 2000Smith et al, 2007), effects mediated by the CNS (Lutz et al, 1995a;Rushing et al, 2000). Previous research has focused heavily on the notion that amylin receptor (AmyR) activation in the area postrema (AP), a hindbrain circumventricular nucleus, is responsible for amylin-induced hypophagia (Lutz et al, 1998;Mollet et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Meal pattern analyses revealed that this effect was mainly due to suppression of meal size, rather than changes to meal frequency, an effect that is consistent with the mechanism of intake suppression produced by peripherally administered amylin receptor agonists (Bello et al, 2008;Lutz et al, 1995b). Thus, it is logical that VTA amylin receptor signaling may control for food intake by modulating the rewarding value of the ongoing meal while having fewer effects on satiety (inter-meal processes).…”
Section: Discussionsupporting
confidence: 55%